Effect of Polymer on Seedling Survival and Growth of Transplanted Tomato Under Water-Stress - GUNES, TOHIT (Asian Journal of Chemistry, 2010)
In this study, effect of water-retentive copolymer, poly(Nvinyl-2-pyrrolidone-crotonic acid) on seedling survival and growth of transplanted tomato has been investigated. 600 Tomato (Lycopersicon esculaentum Mill., cv. 191) seeds were germinated in laboratory and 400 seedlings were used for experiment. Seedlings were transplanted to: (1) soil (2) soil with polymer (3) sand and (4) sand with polymer. This copolymer can retain at least 155 times its weight of water and slowly releases it in 6 d. Hydrogel using significantly effected seedlings survival and growth rate of plants after transplantation. On average, 46, 77, 14 and 38 % of transplanted seedlings survived respectively in soil, soil with hydrogel, sand and sand with hydrogel. Growth rate has been significantly affected by hydrogel using in all growth mediums. The polymer is useful especially in sand medium under water stress and effected seedlings survival more than two-folds.